Implementation of Customer Relationship Management for Quality Improvement Management at "Bima Workshop" (The Indonesian Journal of Business Administration, 2014)
Abstract. â€œBima Workshopâ€ which concern in reparation of engine, certainly the customer service satisfaction must be given main focus by the company. This company has always want to provide the best quality of service but it all can not be separated terms of performance are often unefficiency and uneffectiveness of the process and this can lead to high cost. Based from the Â interview by top management of â€œBima Workshopâ€ obtained Â is often gets complains from customer about the duration of process and the high price of the unit, so it will be do performed analyzes and implementation to improve of the service quality in terms of process and human resources. Analysis is generally done by analysis the benefits of a product (service) and then performed mapping to the customer window who have 4 quadrants (attention, bravo, cut, donâ€™t worry be happy).To find out the root cause of the problem , then analyzed the causal diagram identifying factors that can cause problems with using criteria 7M factors ( manpower , methods , materials , machinery , media and work environment, motivation and money ). To evaluate the performance of the productive commitment to the company, the CRM analysis is divided into 7 categories with the percentage 66.53 % for category 1 ( good ) , category 2 75.43 % ( good ) , category 3 67.86 % ( good ) , category 4 68.98 ( good ) , category 5 61.43 % ( good ) , category 6 48.98 ( mid ) , category 7 53.81 % ( mid ) . Then to evaluate the company's service excellence to the consumer , then the scoring for customer service evaluation and outcome scores obtained value was 41.43 ( mid ). Further analysis of the approach is the reduction of waste which has 8 kinds of criteria (defect, overproduction, waiting, not utilizing, transportation, inventories, motion and excess processing) Â that is It will be used as a basis for planning the waste identification form in order to identifying and eliminate waste. Implementation plan of the recommended action is to do a campaign or briefing about the vision, mission and company goals, market research, documenting the fatal event to the quality improvement worksheet and waste identification form also monitoring performance of the employees in performing in order to work correctly and appropriately, this is all based from evaluating and analyzing that has been done.Â Key Word: Bima Workshop, quality improvement, quality improvements worksheets and waste identification form